(untitled) (Indian Journal of Animal Production and Management, 2016)
An experiment was conducted to study the influence of dietary supplementation of probiotics and enzymes on nutrient digestibilities in broiler rabbits reared under two systems of housing . A total of 144 weaned rabbits were divided into 2 groups of 72 each and housed under conventional cage system and backyard system. The rabbits in each housing system were divided into 4 groups of 18 each. Diet T1 served as control T2 was supplemented with Kemzyme HF @ 500 Ton of feed, Diet T3 was supplemented with Probiotic (S.boulardi50% and P. acidilacticii50%), @109 CFU of feed and Diet T4 contained both probiotics and enzymes at the same concentration. At the end of 16 weeks growth trial, a digestibility trial was conducted for 5 days, to assess the effect of inclusion of probiotics and enzymes on nutrient digestibility. The dry matter intake in rabbits fed rations supplemented with probiotics and enzymes was significantly higher in both the systems of housing. The mean digestibility coefficients of dry matter, organic matter, crude protein, crude fiber, ether extract and nitrogen free extract were 72.64 ± 1.26, 73.10 ± 1.23, 78.61 ± 1.03, 71.59 ± 1.32, 81.12 ± 1.34 and 70.80 ± 1.46 respectively. In both the housing systems, rabbits fed experimental diets recorded significantly higher digestibility coefficients than control group. It was concluded that rabbits can be reared profitably under backyard system and supplementation of probiotics and enzymes had a positive influence on the digestibility of nutrients.